THE RELATIONSHIP BETWEEN STUDENTS’ MOTIVATION AND STUDENTS’ ENGLISH ACHIEVEMENT - Yasmine Purtanto (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The aim of this research was to find out the relationship between students’ motivation and their achievement in learning English. Quantitative method are used in this research. There were 49 students of class VIII in SMP Wahid Hasyim Malang as a participant in this research. In this research, students’ motivation as X variable and students’ English achievement as Y variable. This research used a student motivation questionnaire and an English assignment score document from an English teacher as two instruments. The research procedure consisted of two steps: scoring the questionnaire test and taking the students' assignment scores from the English teacher's document. The researcher used descriptive analysis and Pearson Product Moment Correlation in SPSS 20.0 version to analyze the data. The findings showed that the score of sig (2-tailed = 0.534) < 0.05 means that the relationship between students' motivation and students' achievement in English is not significant at the 0.05 level. Meanwhile, the Pearson Correlation score is 0.091, which means that the relationship between students' motivation and their English achievement is correlated in a very low category. It concluded that there was no significant relationship between students' motivation and their achievement in English. The conclusion shows that students with low motivation do not always get lower scores in English achievement. On the other hand, students with higher motivation do not guarantee that they get higher achievement scores in English.